Scientific production of Nutrition courses in Food and Nutrition in Collective Health: contributions to the debate on professional performance - Taiana Brito Menezes Flor; Luiz Roberto Augusto Noro (Universidade Estadual de Maringá, 2021)
This study aims to analyze the scientific production of Nutrition courses on knowledge core Food and Nutrition in Collective Health (FNCH) and its associations with institutional characteristics and advisor's academic degree. A bibliometric study was performed on 195 final projects of five nutrition courses in Rio Grande do Norte state (Brazil) from the year 2013. Information related to higher education institutions and academic degree of advisor were collected. From the reading of sections of final projects, screening was performed on final project involvement with knowledge core FNCH, being collected general methodological characteristics, classification on sub cores of FNCH, and theme approached. Pearson's chi-square test was used with a significance level at p-value ≤ 0.05 and 95% confidence interval in a univariate and bivariate way. From the total of analyzed final projects, 54 (27.7%) were related to knowledge core FNCH, prevailing final projects with a quantitative approach (61%), presented as scientific articles (57%), and performed in public services (45%). There was an emphasis on the sub-core of Nutritional Epidemiology (63%) [p < 0.001], with the theme Nutritional Assessment (57%) [p < 0.001]. There was no significant association between FNCH final projects proportion and institutional characteristics or advisor's academic degree. Thinking about nutritionists' practice, limitations were identified on FNCH scientific production, with an emphasis on nutritional diagnosis researches, with less involvement in public health policies and human and social sciences.